Coronavirus vaccine - POLAND AGNES; MUIK ALEXANDER; CAI HAIYING; MOGARAD KAVEH; SWANSON KURT A; YANG QIANG; SAHIN UGUR (2024)
The present disclosure relates to the field of RNA for use in the prevention or treatment of coronavirus infection. In particular, the present disclosure relates to methods and agents for vaccinating against coronavirus infections and inducing potent coronavirus antigen-specific immune responses, such as antibody and/or T cell responses. Specifically, in one embodiment, the disclosure relates to a method comprising administering to a subject an RNA encoding a peptide or protein comprising an epitope of the SARS-CoV-2 spike protein (S protein), for inducing in the subject an immune response against a coronavirus S protein, particularly an S protein of SARS-CoV-2, i.e. A vaccine RNA encoding a vaccine antigen. 本公开涉及RNA用于预防或治疗冠状病毒感染的领域。特别地，本公开涉及针对冠状病毒感染进行疫苗接种并诱导有效的冠状病毒抗原特异性免疫反应如抗体和/或T细胞反应的方法和药剂。具体地，在一个实施方案中，本公开涉及包括对受试者施用编码包含SARS-CoV-2刺突蛋白(S蛋白)的表位的肽或蛋白质的RNA，用于在所述受试者中诱导针对冠状病毒S蛋白、特别是SARS-CoV-2的S蛋白的免疫反应，即编码疫苗抗原的疫苗RNA的方法。